Concurrent Ligament and Meniscal Injuries in a 27Year Old Male,Management through Acupuncture an d Cold Knee Pack: A Case Report - Dharuman, Annamalai; N, Prabu; S, Geethanjali; V, Madhumitha; CP, Syam Kumar; B, Abirami (Indian Journal of Integrative Medicine, 2024)
Multiple ligament knee injuries are complex and challenging conditions that often result in longterm impairment and reduced qualityof life for those affected. These injuries commonly involve damage to two or more of the knee's prima ry stabilizing structures,including the anterior cruciate ligament, posterior cruciate ligament, medial collateral ligament, and lateral collateral lig ament. Themanagement of such injuries remains a topic of debate in healthcare. Electro acupuncture and cold packs, a non pharmaceuticaltreatment modality, have shown promising results in the management of musculoskeletal conditions, including ligament injuries . A27 year old patient with concurrent ligament and meniscal injuries, mostly Grade 2 multiple li gament injuries, was givenelectroacupuncture and a cold knee pack 5 times a week for 2 months. The needles used were disposable, sterile, stainless ste el0.25mm x 25mm to a depth of 20 25mm and were inserted perpendicularly at Gall Bladder 34, Spleen 9, S pleen 10, Urinary Bladder40, and Kidney 3 bilaterally. Gall Bladder 34 and Spleen 9 were connected to electroacupuncture for 20 minutes with continuou sstimulation. Followed by a cold knee pack, a 5 feet long, 5 inch wide white cotton cloth dipped in cold water (55º to 65º F), wrappedaround the knee, and then covered with a similarly sized woollen cloth for 20 minutes. Results show that after 2 months of tr eatment,the Visual Analogue Scale (VAS) reduced pain from 8 to 0. The lateral and medial stress tes ts are negative. Magnetic ResonanceImaging (MRI) shows that grade 2 medial collateral ligament injuries become completely normal. Electroacupuncture and cold kn eepacks show promising pain reduction and promote healing.